Lignin-first depolymerization of softwood over a NiCu/TiO2 catalyst for the sustainable production of dihydroconiferyl alcohol - Peng Zhu; Yu-Xin Zhang; Qiang Wang; Guo-Hui Cheng; Jun-Li Ren; Ling-Ping Xiao; Run-Cang Sun (Bioresource Technology, 2026)

Improving ENSO hindcast skill by adjusting the mean background state in a coupled general circulation model (CAS-ESM2.0) - Guixian Li; Guangqing Zhou; Jiangbo Jin; Run Guo; Yuyuan Zhang (Ocean Modelling, 2026)

Molecular adsorption and infrared-driven photocatalytic performance of nitrogen-defective g-C3N4 regulated by Ti doping and oxygen atmosphere treatment - Ziqian Zhang; Ziheng Li; Yu Wang; Yixuan Chen; Yitian Wang; Yuyang Guo; Run Liu; Guancheng Wang; Xingyu Gao; Youyu Pang (Journal of Environmental Chemical Engineering, 2026)

The unintentional adverse effect of Fe3 + on trimethoprim adsorption at environmentally relevant concentration by extracellular polymeric substances - You Ma; Tian-Yu Li; Zi-Yi Fan; Han Meng; Guo-Xiang Wang; Fang Fang; Yu-Dong Chen; Run-Ze Xu; Wen-Ming Xie (Journal of Environmental Chemical Engineering, 2026)

Investigating the therapeutic effects of injectable ammonium glycyrrhizate hydrogel co-loaded with doxorubicin and ATP in triple negative breast cancer - Wanying Chen; Xinyu Liu; Tiantian Guo; Keneng Cai; Wenli Cai; Run Xia; Mengyao Xu; Weichi Jiang; Chuyi Yu; Jianjia Feng; Chengli Ling; Sheng Zhou; et al. (Chemical Engineering Journal, 2026)

Valorization of coffee Silverskin into a novel dietary Fiber ingredient: A comprehensive study on structure, and in vitro/in vivo antioxidant activity - Chen Dai; Run Tang; Ziyu Guo; Weixing Yang; Xiaoyu Gao; Jun Sheng; Yang Tian; Jia Liu (Food Research International, 2026)

Structural features of endogenous polyphenols in modulating oxidative stability of tiger nut (Cyperus esculentus L.) oil: Insights from Rancimat and density functional theory - Zheng-Kai Zhang; Meng-Chen Xie; Jun-Chao Zhang; Lu-Han Sun; Xiao-Shuang Cai; Run-Yang Zhang; Guo-Qiang Zhang; Hua-Min Liu (Food Chemistry, 2026)

One-step scalable synthesis of high-entropy metaphosphate catalysts - Xin Wang; Helong Wu; Weitao Wang; Boyu Huang; Yannan Ye; Lianghou Wu; Sen Wang; Run Huang; Panjie Guo; Lei Wang (Chemical Engineering Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Mechanistic insights into triclocarban-induced skin barrier disruption via integrating imaging localization, multi-omics, and network toxicology - Jingwen Zheng; Run Guo; Rong Zhang; Xinyu Liu; Rouyue Guo; Haozheng Li; Juntong Wei; Yuxin Zheng; Hongna Zhang (Environmental Pollution, 2026)

A subset of endogenous P2X5 transcripts encodes ATP-sensitive receptor isoforms - Xiao-Na Yang; Dong-Ping Wang; Chen-Hui Shen; Xi Chen; Ai-Xin Zhang; Meng Zhang; Xing Zhou; Yun Tian; Peng Cao; Michael X. Zhu; Hui Yang; Chang-Run Guo; et al. (Science Bulletin, 2026)

ClO₂-induced VBNC state in Enterococcus faecalis poses a health risk in drinking water systems - Ziyi Zhang; Shuai Cheng; Menghua Duan; Yihong Wang; Weipeng Xu; Yiming Lu; Hui Yang; Na Lv; Run Ma; Jiahui Guo; Chao Shi (Journal of Hazardous Materials, 2026)

Catchment topography and land cover modulate DOM photoreactivity in reservoirs - Run Zhang; Zhongyu Guo; Guo Chen; Ye Zhang; Hidetaka Ichiyanagi; Chihiro Yoshimura (Journal of Environmental Management, 2026)

Physicochemical properties, antioxidant activity, antibacterial properties, and fruit preservation potential of black soldier fly chitosan films - Bin-Qiao Yuan; Ting-Hao Yu; Jun-Kui Huang; Xin-Rui Ren; Run-Jia Wang; Guo-Xin Huang; Nortoji A. Khujamshukurov; Da-Wei Huang; Jin-Hua Xiao (Food Bioscience, 2026)

Correction to: CAS-ESM2.0 Dataset for the Carbon Dioxide Removal Model Intercomparison Project (CDRMIP) - Jiangbo Jin; Duoying Ji; Xiao Dong; Kece Fei; Run Guo; Juanxiong He; Yi Yu; Zhaoyang Chai; He Zhang; Dongling Zhang; Kangjun Chen; Qingcun Zeng (Advances in Atmospheric Sciences, 2026)

DrPISA: Deep eutectic solvent-assisted reverse proteome-integrated solubility alteration for high-sensitivity drug target identification - Liu Yang; Tian-Bo Ma; Chen-Wan Guo; Run-Bo Yu; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2026)

Experimental investigation on adiabatic two-phase frictional pressure drop of R290, R600a, and their mixtures in a horizontal minichannel - Na Liu; Hao Ji; Yeyi Liu; Run Li; Dezheng Sun; Qian Zhao; Jianxiang Guo (International Journal of Refrigeration, 2026)

Simulation-to-Reality transfer learning with UAV-based imagery for forest inventory attribute prediction - Qing Guo; Linyuan Li; Run Yu; Zhuangzhuang Zhang; Huaguo Huang (Computers and Electronics in Agriculture, 2026)

Unlocking the potential of high-entropy catalysts in selective electrocatalytic organic transformations - Meng Dan; Yu-Qi Zhang; Tao Wei; Run-Long Qi; Shishan Xue; Zhen Guo; Zhao-Qing Liu (Science Bulletin, 2026)

Chitosan/gelatin-based film activated by Pickering emulsion of citrus essential oil stabilized by esterified starch/whey protein isolate fibrils: Application in preserving freshness of blueberry - Run Ji; Hao Guo; Xu Yang; Lepei Wang; Xiuling Zhang; Hui Zhang (Food Chemistry, 2026)

Pyrogenic carbon-stimulated nitrate-dependent anaerobic methane oxidation: insights into redox activity and conductivity in anaerobic methanotrophic archaea metabolism and microbial dynamics - Fangrui Cai; Yu Wang; Mengying Xie; Guanbin Li; Suicao Wang; Venea Dara Daygon; Dihua Tian; Gaofeng Ni; Xiang Liu; Run Zhang; Lirong Lei; Zhiguo Yuan; et al. (Water Research, 2026)

Decaprenyl diphosphate synthases in Monolepta hieroglyphica: DPPS-mediated CoQ biosynthesis impacts juvenile hormone and gut microbiota - Xuan Song; Jun-feng Kou; Chang Liu; Yong Yang; Da-wei Zhang; Chao-qun Yi; Wen-tao Liu; Run Chen; Wei-hao Guo; Yue-qin Wang; Tian-tao Zhang; Yong-jun Zhang (Insect Biochemistry and Molecular Biology, 2025)

A study on soil erodibility and the applicability of estimation methods in Robinia pseudoacacia L. mixed forests on the Loess Plateau, China - Jin-long Ma; Bing Wang; Run-hao Yu; Yan-fen Yang; Guo-bin Liu; Jing Wang; Cheng-fang Li (CATENA, 2025)

Ball-milling treated superfine powdered activated carbon triggers Mn(VII) activation for enhanced oxidation of organic contaminants - Run Huang; Chaoting Guan; Qin Guo; Jin Jiang (Water Research, 2025)

Iridoids and other constituents from the aerial parts of Patrinia rupestris and their inhibitory effects on nitric oxide production - Zhi-Yuan Liu; Sheng-Run Guo; Jian-Xian Tang; Chun-Yan Zhao; Li Pu; Li-Zhong Wang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2025)

pH-regulated structural and interfacial properties of OSA starch/whey protein fiber complexes to improve the storage and digestive stability of citrus essential oil emulsions - Run Ji; Haowen Sun; Zhao Chen; Shuang Song; Hao Guo; Xiuling Zhang; Fei Wu (Carbohydrate Polymers, 2025)

Waste biomass-derived organic matter for sustainable soil remediation: Enhancing heavy metal removal and eluent reuse in agricultural application - Shuai Yang; Chen Tu; Guo-ming Liu; Yuan Li; Yi Wang; Xia Zhu; Shao-cheng Si; Run-lai Luo; Zhong-yuan Li; Yong-ming Luo (Bioresource Technology, 2025)

Response of phytoplankton productivity to in-situ measures against eutrophication in reservoirs of Japan in recent decades - Zhang Ye; Chen Guo; Hidetaka Ichiyanagi; Zhang Xiaoxuan; Zhang Run; Chihiro Yoshimura (Journal of Environmental Management, 2025)

A portable slide based MIPs-FL sensor was fabricated for potential on-site detection - Run-tian Ma; Jun Zhang; Jin-xiu Guo; Fang Nian; Cheng Wang; Wei-bing Xu (Food Chemistry, 2025)

Enzyme treatment combined with Maillard reaction modification of sunflower meal hydrolysates to prepare sunflower seed oil flavor enhancer - Shuai Xu; Qing Guo; Yu-Xuan Jin; Run-Yang Zhang; Hua-Min Liu; Zhao Qin; Xiu-Zhu Yu; Xue-De Wang (Food Chemistry, 2025)

Divergent effects of cropland management practices and global change factors on microbial necromass across ecosystems: implications for soil organic carbon - Chen-Hao Lyu; Wen-Jun He; Peng Chen; Xin-Xin Jing; Guo-Shi Zhang; Run-Qin Zhang; Zi-Yan Li; Zhi-Guo Li; Yi Liu (CATENA, 2025)

Intelligent active double-layer film based on ɛ-polylysine-anthocyanin co-pigmentation effect and Zn‑carbon dot construction: Effects on pork preservation, freshness monitoring and soil microbiology - Run Ji; Shuang Song; Lepei Wang; Hao Guo; Xiuling Zhang; Wentao Zhang (Chemical Engineering Journal, 2025)

Geochemistry characteristics and tectonic significance of the ‘ “mafic” S-type granites’ - Qiang Shi; Xiang-Zhi Chen; Run-Xiao Shu; Yu-Song Chen; Shi-Jie Wang; Zhong-Yuan Xu; Kai-Yun Chen; Guo-Chun Zhao (International Geology Review, 2025)

A wireless and passive RFID tag sensor for the detection of Pb2+ in soil combining chemiresistive sensing and impedance mismatch: A new method for onsite detection of hazardous metals - Hao Wang; Zuozheng Ding; Xingping Wang; Zaihan Zou; Run Zhang; Yunda Chen; Xiaochan Wang; Guo Zhao (Journal of Hazardous Materials, 2025)

Elucidating the influence of alumina mineral on sodium storage performance of biomass-derived hard carbon anode - Hang Guo; Jia-He Lv; Run-Dong He; Bin He; Xiao-Ling Dong; Wen-Cui Li (Fuel, 2025)

Arbuscular mycorrhizal fungi enhance Leymus chinensis resistance to salinity predominantly through regulating root endosphere bacteria - Peiran Guo; Yazhou Hou; Bingbing Jia; Yuchen Wang; Chengyan Lu; Run Wang; Jiaying Lin; Yanan Zhang; Wei Guo; Frank Yonghong Li (Plant and Soil, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Enhanced activation of peroxymonosulfate by nickel sulfide with sulfur vacancies for ultrafast organic pollutants degradation: Roles of active sites and mechanism - Cai-Wu Luo; Liang Jiang; Xian-Feng Li; Qiang-Mao Wan; Tian-Jiao Jiang; Sen-Ping Mao; Jing-Qian Guo; Run-Ze Zhao; Chao Xie (Environmental Pollution, 2025)

Reexamination and reidentification of ocean oxygenation event in the wake of the Marinoan glaciation - Run Li; Xiqiang Zhou; Chuan Guo; Taiyu Huang; Zhenfei Wang; Kang-Jun Huang; Peng Peng; Xiangli Wang; Tongxuan Du; Dingshuai Xue; Yanhong Liu (Earth and Planetary Science Letters, 2025)

Ecoenzymatic stoichiometry reveals the exacerbation of microbial C and N limitations by moss crusts in degraded karst ecosystems - Minghao Deng; Jiaojiao Wu; Xin Zhao; Dong Chen; Guanting Guo; Mingzhong Long; Qimei Wu; Run Liu; Xiaona Li (Applied Soil Ecology, 2025)

Three new maaliane-type sesquiterpenoids from the roots and rhizomes of Valeriana officinalis var. latifolia - Jia-Jin Liu; Sheng-Run Guo; Hou Zhu; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry Letters, 2025)

Endophytes and soil microorganisms participate in the germination of Sinojackia xylocarpa Hu by degrading the pericarp - Zi-Hao Li; Xin-Yi Ma; Huan Yang; Run-Guo Zang; Jia-Ru Li (Acta Physiologiae Plantarum, 2025)

Neferine induces apoptosis and inhibits metastasis in human endometrial cancer cells by down-regulating miR-1266–5p - Fei-Fei Ma; Run-Hui Ma; Wang-Wei Zhang; Xiu-Xiu Zhang; Qian Zhong; Kiran Thakur; Jian-Guo Zhang; Jesus Simal-Gandara; Hui Cao (Food Bioscience, 2025)

Layer-by-layer nanoencapsulation strategies for enhanced oral delivery and function of Lactobacillus plantarum B2 - Yun-Yang Zhu; Run-Hui Ma; Kiran Thakur; Wang-Wei Zhang; Jian-Guo Zhang; Mohammad Rizwan Khan; Chenzhong Liao; Zhao-Jun Wei (Food Hydrocolloids, 2025)

Paleoproterozoic granite in the Khondalite Belt, northern margin of the North China Craton: Response to the assembly of the Columbia supercontinent - Qiang Shi; Run-Xiao Shu; Xiang-Zhi Chen; Guo-Chun Zhao; Yu-Song Chen; Zhao-Sheng Wang; Long Ma; Zhong-Yuan Xu; Zheng-Hong Liu; Kai-Yun Chen; Hui-Chu Wang (Precambrian Research, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Kopsileuconines A−D: Bisindole alkaloids with cytotoxic activity from Kopsia hainanensis - Ni-Ping Li; Shan-Na Chen; Wei-Fang Su; Fen Liu; Lian-Jing Li; Jian-Guo Song; Min-Jing Cheng; Yi-Yi Li; Run-Qiang Chen; Xue-Ping Lei; Wen-Cai Ye; Lei Wang (Phytochemistry, 2024)

Anaerobic oxidation of methane coupled to reductive immobilization of hexavalent chromium by “Candidatus Methanoperedens” - Suicao Wang; Xueqin Zhang; Dihua Tian; Jing Zhao; Hesamoddin Rabiee; Fangrui Cai; Mengying Xie; Bernardino Virdis; Jianhua Guo; Zhiguo Yuan; Run Zhang; Shihu Hu (Journal of Hazardous Materials, 2024)

Synergistic defects and structural reconstruction in S-scheme Bi2MoO6-x-TiO2 heterojunction for enhancing piezo-photocatalytic degradation of gatifloxacin - Ruixin Chen; Wei Gan; Jun Guo; Sheng Ding; Run Liu; Ziwei Zhao; Kui Yan; Zihan Zhou; Miao Zhang; Zhaoqi Sun (Chemical Engineering Journal, 2024)

Laminar burning characteristics of ammonia and hydrogen blends at elevated initial pressures up to 2.5 MPa - Ning Wang; Tie Li; Xinpeng Guo; Zehao Wu; Shuai Huang; Xinyi Zhou; Shiyan Li; Run Chen (Chemical Engineering Journal, 2024)

Enhanced extraction of Mg (Ⅱ) and mass transfer characteristics in planar mesh-segmented microchannel - Yong Suo; Zini Guo; Shan Wang; Run Liu; Quanwu Guo; Jianhong Luo (Chemical Engineering Journal, 2024)

Aerobic granular sludge for swine wastewater treatment: Implications for antibiotic and antibiotic resistance gene elimination - Meng-Yuan Li; Run-Dong Zhang; Shuang-Shuang Liu; Cheng-Lei Pei; Liang-Ying He; Jian-Liang Zhao; You-Sheng Liu; Yi-Jing Shi; Guang-Guo Ying (Bioresource Technology, 2024)

Experimental Study on Multistage Seismic Damage Process of Bedding Rock Slope: A Case Study of the Xinmo Landslide - Jing-Jing Tian; Tian-Tao Li; Xiang-Jun Pei; Jian Guo; Shou-Dao Wang; Hao Sun; Pei-Zhang Yang; Run-Qiu Huang (Journal of Earth Science, 2024)

Metagenomic investigation of antibiotic resistance genes and resistant bacteria contamination in pharmaceutical plant sites in China - Run-Dong Zhang; Fang-Zhou Gao; Yi-Jing Shi; Jian-Liang Zhao; You-Sheng Liu; Liang-Ying He; Guang-Guo Ying (Environmental Pollution, 2024)

An innovative dynamic anomaly detection method based on hybrid data mining technology for building energy consumption - Lei Lei; Xuesong Guo; Run Zheng (Energy and Buildings, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Response of soil aggregate-associated fertility and microbial communities to afforestation in the degraded ecosystem of the Danjiangkou Reservoir, China - Peng Chen; Li Wang; Jun-Ya Li; Wenjie Wan; Run-Qin Zhang; Yi Liu; Zhi-Guo Li (Plant and Soil, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Produce low-CO2 silica fume hybrid high-strength concrete using dry ice (solid CO2) as a CO2-utilized admixture - Mei-Yu Xuan; Run-Sheng Lin; Yi Han; Gui-yu Zhang; Cheng Guo; Xiao-Yong Wang (Journal of Cleaner Production, 2024)

Internal electric field and oxygen vacancies synergistically boost S-scheme VO/BiOCl-TiO2 heterojunction film for photocatalytic degradation of norfloxacin - Ruixin Chen; Wei Gan; Jun Guo; Yuqing Lu; Sheng Ding; Run Liu; Miao Zhang; Zhaoqi Sun (Chemical Engineering Journal, 2024)

Advances in biotin biosynthesis and biotechnological production in microorganisms - Jia-Run Zhao; Si-Qi Zuo; Feng Xiao; Feng-Zhu Guo; Lu-Yi Chen; Ke Bi; Dong-Yuan Cheng; Zhi-Nan Xu (World Journal of Microbiology and Biotechnology, 2024)

CAS-ESM2.0 Dataset for the Carbon Dioxide Removal Model Intercomparison Project (CDRMIP) - Jiangbo Jin; Duoying Ji; Xiao Dong; Kece Fei; Run Guo; Juanxiong He; Yi Yu; Zhaoyang Chai; He Zhang; Dongling Zhang; Kangjun Chen; Qingcun Zeng (Advances in Atmospheric Sciences, 2024)
Understanding the response of the Earth system to varying concentrations of carbon dioxide (CO 2 ) is critical for projecting possible future climate change and for providing insight into mitigation and adaptation strategies in the near future. In this study, we generate a dataset by conducting an experiment involving carbon dioxide removal (CDR)—a potential way to suppress global warming—using the Chinese Academy of Sciences Earth System Model version 2.0 (CAS-ESM2.0). A preliminary evaluation is provided. The model is integrated from 200–340 years as a 1% yr −1 CO 2 concentration increase experiment, and then to ~478 years as a carbon dioxide removal experiment until CO 2 returns to its original value. Finally, another 80 years is integrated in which CO 2 is kept constant. Changes in the 2-m temperature, precipitation, sea surface temperature, ocean temperature, Atlantic meridional overturning circulation (AMOC), and sea surface height are all analyzed. In the ramp-up period, the global mean 2-m temperature and precipitation both increase while the AMOC weakens. Values of all the above variables change in the opposite direction in the ramp-down period, with a delayed peak relative to the CO 2 peak. After CO 2 returns to its original value, the global mean 2-m temperature is still ~1 K higher than in the original state, and precipitation is ~0.07 mm d −1 higher. At the end of the simulation, there is a ~0.5°C increase in ocean temperature and a 1 Sv weakening of the AMOC. Our model simulation produces similar results to those of comparable experiments previously reported in the literature.

Offshore Renewable Energy - Jijian Lian; Qiang Fu; Lin Cui; Run Liu; Bingyong Guo (Journal of Marine Science and Engineering, 2024)
Offshore renewable energy is an abundant clean energy source that includes offshore solar energy, offshore wind power, wave energy, ocean thermal energy conversion (OTEC), and tidal energy [...]

An observation-based analysis of atmospheric oxidation capacity in Guangdong, China - Liyan Wei; Run Liu; Chungui Liao; Shanshan Ouyang; Yanxing Wu; Bin Jiang; Duohong Chen; Tao Zhang; Yan Guo; Shaw Chen Liu (Atmospheric Environment, 2024)

Lycium barbarum (Goji) as functional food: a review of its nutrition, phytochemical structure, biological features, and food industry prospects - Run-Hui Ma; Xiu-Xiu Zhang; Zhi-Jing Ni; Kiran Thakur; Wei Wang; Ya-Mei Yan; You-Long Cao; Jian-Guo Zhang; Kannan R. R. Rengasamy; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2023)

Soil aggregate-associated organic carbon mineralization and its driving factors in rhizosphere soil - Jun-Ya Li; Peng Chen; Zhi-Guo Li; Lin-Yang Li; Run-Qin Zhang; Wei Hu; Yi Liu (Soil Biology and Biochemistry, 2023)

Study on liquid dispersion characteristics in trickle bed reactor based on image processing - Run Guo; Bin Wei; Huanzhi Liu; Xiaogang Shi; Xingying Lan; Jinsen Gao (Fuel, 2023)

Structural plane recognition from three-dimensional laser scanning points using an improved region-growing algorithm based on the robust randomized Hough transform - Zhi-hua Xu; Ge Guo; Qian-cheng Sun; Quan Wang; Guo-dong Zhang; Run-qing Ye (Journal of Mountain Science, 2023)

The Effects of Wave-Induced Stokes Drift and Mixing Induced by Nonbreaking Surface Waves on the Ocean in a Climate System Ocean Model - Peng Fan; Jiangbo Jin; Run Guo; Guixian Li; Guangqing Zhou (Journal of Marine Science and Engineering, 2023)
Oceanic general circulation models (OGCMs) are important tools used to investigate mechanisms for ocean climate variability and predict the ocean change in the future. However, in most current ocean models, the impact of sea surface waves as one of the most significant dynamic processes in the upper ocean is absent. In this study, the Stokes drift and the vertical mixing induced by nonbreaking surface waves derived from the wave model (WAVEWATCH III) are incorporated into a Climate System Ocean Model, and their effects on an ocean climate simulation are analyzed. Numerical experiments show that both physical processes can improve the simulation of sea surface temperature (SST) and mixed layer depth (MLD) in the Southern Hemisphere. The introduction of Stokes drift effectively reduces the subsurface warm bias in the equatorial tropics, which is caused by the weakening of vertical mixing in the equatorial region. The nonbreaking surface wave mainly reduces the temperature bias in the Southern Ocean by enhancing mixing in the upper ocean. For the MLD, the Stokes drift mainly improves the simulation of the winter MLD, and the nonbreaking surface wave improves the summer MLD. For MLD south of 40° S in summer, the introduction of nonbreaking surface waves resulted in a reduction of 11.86 m in MLD bias and 7.8 m in root mean square errors (RMSEs), respectively. For winter subtropical MLD in the Southern Hemisphere, considering the Stokes drift, the MLD bias and RMSEs were reduced by 2.49 and 5.39 m, respectively. Adding these two physical processes simultaneously provides the best simulation performance for the structure of the upper layer. The introduction of sea surface waves effectively modulates the vertical mixing of the upper ocean and then improves the simulation of the MLD. Thus, sea surface waves are very important for ocean simulation, so we will further couple a sea waves model in the Chinese Academy of Sciences Earth System Model (CAS-ESM) as part of their default model component.

Isolation and Identification of a Phosphate-Solubilizing Pantoea dispersa with a Saline–Alkali Tolerance and Analysis of Its Growth-Promoting Effects on Silage Maize Under Saline–Alkali Field Conditions - Ying Cui; Yujie Zhao; Run Cai; Hao Zhou; Jiaxin Chen; Lirong Feng; Changhong Guo; Dan Wang (Current Microbiology, 2023)

Construction ceramsite from low-silicon red mud: Design, preparation, and sintering mechanism analysis - Zhuo Liu; Rongxin Guo; Xiao-Yong Wang; Chaoshu Fu; Run-sheng Lin (Process Safety and Environmental Protection, 2023)

Determination of 63 mycotoxins in grain products by ultrahigh-performance liquid chromatography coupled with quadrupole-Orbitrap mass spectrometry - Wenlin Wu; Xia Huang; Run Liang; Tianrong Guo; Quanwei Xiao; Bing Xia; Yuping Wan; Yan Zhou (Food Control, 2023)

Evolutionary research trend of Polygonatum species: a comprehensive account of their transformation from traditional medicines to functional foods - Xiao-Li Li; Run-Hui Ma; Fan Zhang; Zhi-Jing Ni; Kiran Thakur; Shaoyun Wang; Jian-Guo Zhang; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2023)

Synergistic mechanisms of bioorganic fertilizer and AMF driving rhizosphere bacterial community to improve phytoremediation efficiency of multiple HMs-contaminated saline soil - Chengyan Lu; Zhechao Zhang; Peiran Guo; Run Wang; Tai Liu; Junqing Luo; Baihui Hao; Yuchen Wang; Wei Guo (Science of The Total Environment, 2023)

Eugenilones A−N: sesquiterpenoids from the fruits of Eugenia uniflora - Mu Chen; Run-Qiang Chen; Yuan Guo; Jian-Xin Chen; Qian Jin; Mei-Hong Chen; Bo-Yong Chen; Zheng-Chao Tu; Wen-Cai Ye; Lei Wang (Phytochemistry, 2023)

Structural characterization and stability of glycated bovine serum albumin-kaempferol nanocomplexes - Run-Hui Ma; Wei Wang; Cai-Ping Hou; Yi-Fei Man; Zhi-Jing Ni; Kiran Thakur; Jian-Guo Zhang; Zhao-Jun Wei (Food Chemistry, 2023)

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Failure mechanism of a large-scale composite deposits caused by the water level increases - Xin Zhang; Guo-xiang Tu; Qi-feng Luo; Hao Tang; Yu-lin Zhang; An-run Li (Journal of Mountain Science, 2023)

Bioorganic fertilizers improve the adaptability and remediation efficiency of Puccinellia distans in multiple heavy metals-contaminated saline soil by regulating the soil microbial community - Run Wang; Tai Liu; Chengyan Lu; Zhechao Zhang; Peiran Guo; Bingbing Jia; Baihui Hao; Yuchen Wang; Wei Guo (Journal of Hazardous Materials, 2023)

Preparation of mixed matrix membranes by layered double hydroxides of amino acid intercalation and Pebax for ameliorated CO2 separation - Hui Guo; Shaohan Lian; Run Li; Yijuan Zhang; Quan Zhao; Chunfeng Song (Journal of Environmental Chemical Engineering, 2023)

How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China - Meng-Xue Tang; Xiao-Feng Huang; Pei-Ting Yao; Run-Hua Wang; Zhi-Jie Li; Chao-Xi Liang; Xing Peng; Li-Ming Cao; Ke Du; Kuangyou Yu; Song Guo (Atmospheric Environment, 2023)

Variations in the concentration, source and flux of polycyclic aromatic hydrocarbons in sediments of the Pearl River Estuary: Implications for anthropogenic impacts - Yali Li; Nairong Guo; Ke Yuan; Baowei Chen; Junjie Wang; Maofeng Hua; Jing Yu; Jingyan Hu; Run Lu; Shichun Zou; Ying Yang (Science of The Total Environment, 2023)

Liraglutide inhibits AngII-induced cardiac fibroblast proliferation and ECM deposition through regulating miR-21/PTEN/PI3K pathway - Jun Wang; Run Guo; Xiaoli Ma; Ying Wang; Qianyu Zhang; Nan Zheng; Jun Zhang; Chenchen Li (Cell and Tissue Banking, 2023)

Biotransformation of sulfamonomethoxine in a granular sludge system: Pathways and mechanisms - Meng-Yuan Li; Run-Dong Zhang; Yi-Xing Lin; Qi-Wen Li; Qiu-Yue Zhao; Zong-Xi Zhao; Zhong-Ming Ling; Long-Fei Shu; Min Zhang; Li-Xin Hu; Yi-Jing Shi; Guang-Guo Ying (Chemosphere, 2023)

Seasonal spermatogenesis, epididymal storage, and creatine kinase expression in Pelodiscus sinensis - Yu-Fei Yang; Jia-Hao Wu; Run-Lan Lin; Shang-Jun Yin; Guo-Ying Qian; Wei Wang; Yong-Doo Park (Animal Reproduction Science, 2023)

Gastrodin Attenuates Lipopolysaccharide-Induced Inflammatory Response and Migration via the Notch-1 Signaling Pathway in Activated Microglia - Yue-yi Yao; Run Li; Yan-ji Guo; Yu Zhao; Jia-zhi Guo; Qing-long Ai; Lian-mei Zhong; Di Lu (NeuroMolecular Medicine, 2022)

A New Species of Paradiplozoon (Monogenea: Diplozoidae), A Gill Parasite of the Schizothorax Fish (Cyprinidae: Schizothoracinae) from the Yarkand River, Xinjiang, China - Kadirden Arken; Cui-Lan Hao; Ai-Ming Guo; Wen-Run Zhang; Meng-Jie Rong; Wuljan Kamal; Sheng-Li Tian; Munira Kadir; Cheng Yue (Acta Parasitologica, 2022)

The decreased expression of GW2 homologous genes contributed to the increased grain width and thousand‑grain weight in wheat-Dasypyrum villosum 6VS·6DL translocation lines - Zhiyu Feng; Long Song; Wanjun Song; Zhongqi Qi; Jun Yuan; Run Li; Haiming Han; Huifang Wang; Zhaoyan Chen; Weilong Guo; Mingming Xin; Jie Liu; et al. (Theoretical and Applied Genetics, 2021)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Landslide mapping and analysis along the China-Pakistan Karakoram Highway based on SBAS-InSAR detection in 2017 - Xiao-jun Su; Yi Zhang; Xing-min Meng; Dong-xia Yue; Jin-hui Ma; Fu-yun Guo; Zi-qiang Zhou; Mohib Ur Rehman; Zainab Khalid; Guan Chen; Run-qiang Zeng; Fu-meng Zhao (Journal of Mountain Science, 2021)

Effect of the number of coplanar rock bridges on the shear strength and stability of slopes with the same discontinuity persistence - Peng Tang; Guo-Qing Chen; Run-Qiu Huang; Dong Wang (Bulletin of Engineering Geology and the Environment, 2021)

Numerical simulation of seasonal snow in Tianshan Mountains - Yan-run Ren; Yao-nan Zhang; Jian-sheng Hao; Yong-ping Shen; Guo-hui Zhao; Cong Li (Journal of Mountain Science, 2021)

Study on NOx removal from simulated flue gas by an electrobiofilm reactor: EDTA-ferrous regeneration and biological kinetics mechanism - Nan Liu; Ying-ying Li; Du-juan Ouyang; Rui Guo; Run Chen; Wei Li; Ji-xiang Li; Ji-hong Zhao (Environmental Science and Pollution Research, 2021)

Brittle failure of rockslides linked to the rock bridge length effect - Peng Tang; Guo-Qing Chen; Run-Qiu Huang; Jing Zhu (Landslides, 2020)

Physical Model Experimental Study on Spalling Failure Around a Tunnel in Synthetic Marble - Guo-Qiang Zhu; Xia-Ting Feng; Yang-Yi Zhou; Zheng-Wei Li; Lian-Jie Fu; Yong-Run Xiong (Rock Mechanics and Rock Engineering, 2020)

Numerical modeling of the 2008 Wenchuan earthquake-triggered Niumiangou landslide considering effects of pore-water pressure - Da Huang; Yi Xiang Song; Guo Wei Ma; Xiang Jun Pei; Run Qiu Huang (Bulletin of Engineering Geology and the Environment, 2019)

Protection of melon against Fusarium wilt-root knot nematode complex by endophytic fungi Penicillium brefeldianum HS-1 - Guo-peng Miao; Juan Han; Ke-gui Zhang; Shun-chang Wang; Cheng-run Wang (Symbiosis, 2019)

Evaluation of the possible slip surface of a highly heterogeneous rock slope using dynamic reduction method - Guo-qing Chen; Run-qiu Huang; Feng-shou Zhang; Zhen-fei Zhu; Yu-chuan Shi; Jian-chao Wang (Journal of Mountain Science, 2018)

Identification and mapping of ts (tender spines), a gene involved in soft spine development in Cucumis sativus - Chunli Guo; Xuqin Yang; Yunli Wang; Jingtao Nie; Yi Yang; Jingxian Sun; Hui Du; Wenying Zhu; Jian Pan; Yue Chen; Duo Lv; Huanle He; et al. (Theoretical and Applied Genetics, 2018)

Distribution and mechanism of gently dipping fractures subjected to river incision: A case study from Nujiang River, China - Lei Zhu; Run-qiu Huang; Ming Yan; Guo-qing Chen; Wei Wei (Journal of Mountain Science, 2018)

Geological analysis of gravitational rock slope deformation: a case from Nujiang River, China - Lei Zhu; Run-qiu Huang; Ming Yan; Guo-qing Chen (Journal of Mountain Science, 2017)

The In vitro/vivo Evaluation of Prepared Gastric Floating Tablets of Berberine Hydrochloride - Jun Ji; Xin He; Xiao-Lin Yang; Wen-Juan Du; Cheng-Long Cui; Ling Wang; Xue Wang; Chun-Feng Zhang; Chang-Run Guo (AAPS PharmSciTech, 2017)

Effect of rainfall on a colluvial landslide in a debris flow valley - Liang Qiao; Xing-min Meng; Guan Chen; Yi Zhang; Peng Guo; Run-qiang Zeng; Ya-jun Li (Journal of Mountain Science, 2017)

Skarn mineralogy and its geological significance for the Tayuan (Cu–Mo)–Pb–Zn deposit, northern Daxinganling metallogenic belt - Chao Li; Tao Ren; Jian-Guo Huang; Run-Sheng Han; He-Jun Yin; Hong-Yang Zhou; Zhi-Hong Feng (Acta Geochimica, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Identification and mapping of Tril, a homeodomain-leucine zipper gene involved in multicellular trichome initiation in Cucumis sativus - Yun-Li Wang; Jing-tao Nie; Hui-Ming Chen; Chun-li Guo; Jian Pan; Huan-Le He; Jun-Song Pan; Run Cai (Theoretical and Applied Genetics, 2016)

Sediment delivery across multiple spatio-temporal scales in an agriculture watershed of the Chinese Loess Plateau - Ming-guo Zheng; Run-kui Li; Ji-jun He; Ming Cui (Journal of Mountain Science, 2015)

Expression profiles of miRNAs in Gossypium raimondii - Jun Ma; Teng-long Guo; Qing-lian Wang; Kun-bo Wang; Run-run Sun; Bao-hong Zhang (Journal of Zhejiang University-SCIENCE B, 2015)

Scale Effects on Spatially Varying Relationships Between Urban Landscape Patterns and Water Quality - Yanwei Sun; Qinghai Guo; Jian Liu; Run Wang (Environmental Management, 2014)

Evolution of High-Affinity Peptide Probes to Detect the SH3 Domain of Cancer Biomarker BCR–ABL - Hui-Min Liu; Li-Juan Li; Juan Guo; Zhan-Jia Yang; Xiao Yang; Run-Peng Qi; Wei Cao (International Journal of Peptide Research and Therapeutics, 2014)

High seroprevalence of Chlamydia infection in sows in Hunan province, subtropical China - Xiao-Xuan Zhang; Run-Cheng Li; Guo-Hua Liu; Wei Cong; Hui-Qun Song; Xing-Long Yu; Xing-Quan Zhu (Tropical Animal Health and Production, 2014)

Progressive modelling of the gravity-induced landslide using the local dynamic strength reduction method - Guo-qing Chen; Run-qiu Huang; Qiang Xu; Tian-bin Li; Ming-lei Zhu (Journal of Mountain Science, 2013)
The failure of slope is a progressive process, and the whole sliding surface is caused by the gradual softening of soil strength of the potential sliding surface. From this viewpoint, a local dynamic strength reduction method is proposed to capture the progressive failure of slope. This method can calculate the warning deformation of landslide in this study. Only strength parameters of the yielded zone of landslide will be reduced by using the method. Through continuous local reduction of the strength parameters of the yielded zone, the potential sliding surface developed gradually and evolved to breakthrough finally. The result shows that the proposed method can simulate the progressive failure of slope truly. The yielded zone and deformation of landslide obtained by the method are smaller than those of overall strength reduction method. The warning deformation of landslide can be obtained by using the local dynamic strength reduction method which is based on the softening characteristics of the sliding surface.

Permeability and sedimentation characteristics of pleistocene fluvio-glacial deposits in the Dadu river valley, Southwest China - Guo-xiang Tu; Run-qiu Huang; Hui Deng; Yan-rong Li (Journal of Mountain Science, 2013)

Acute Clenbuterol Induces Hypotension, Atrioventricular Block and Cardiac Asystole in the Rabbit - Yan Ke; Li-Lan Fu; Xia-Fei Hong; Run Dong; Tian-Ming Xu; Jing-Fei Guo; Yan Liu; Ji-Min Cao (Cardiovascular Toxicology, 2013)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

Comparative ecophysiological responses to drought of two shrub and four tree species from karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Guo-Qing Li; Yuan-Run Zheng; Li-Fei Yu; Rui Yang (Trees, 2011)

Screening Level of PAHs in Sediment Core from Lake Hongfeng, Southwest China - Jian-Yang Guo; Feng-Chang Wu; Liang Zhang; Hai-Qing Liao; Run-Yu Zhang; Wei Li; Xiao-Li Zhao; She-Jun Chen; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2011)

RRM1 gene expression in peripheral blood is predictive of shorter survival in Chinese patients with advanced non-small-cell lung cancer treated by gemcitabine and platinum - Lin-run Wang; Guo-bing Zhang; Jian Chen; Jun Li; Ming-wei Li; Nong Xu; Yang Wang; Jian-zhong Shen Tu (Journal of Zhejiang University-SCIENCE B, 2011)

Improvement of acetic acid tolerance and fermentation performance of Saccharomyces cerevisiae by disruption of the FPS1 aquaglyceroporin gene - Jun-Guo Zhang; Xiu-Ying Liu; Xiu-Ping He; Xue-Na Guo; Ying Lu; Bo-run Zhang (Biotechnology Letters, 2011)

Effects of exogenous putrescine on gas-exchange characteristics and chlorophyll fluorescence of NaCl-stressed cucumber seedlings - Run Hua Zhang; Jun Li; Shi Rong Guo; Takafumi Tezuka (Photosynthesis Research, 2009)

Arbuscular mycorrhizal fungi associated with common pteridophytes in Dujiangyan, southwest China - Run-Jin Liu; Ying Zhang; Liang-Dong Guo (Mycorrhiza, 2004)

Study on canopy disturbance regime and mechanism of tree species diversity maintenance in the lower subtropical evergreen broad-leaved forest, South China - Zang Run-Guo; Wang Bo-Sun (Plant Biosystems, 2002)